Exploring students' experience with game-based learning: a descriptive study. - Sharmin, Nazlee; Shah, Malav; Chow, Ava K. (Canadian Journal of Dental Hygiene, 2025)
Background: Game-based learning aims to promote student engagement and boost motivation in the classroom. However, creating long-term motivation in an education game is challenging and requires a balance between "fun" and "educational" objectives. The gaming platform Gimkit allows educators to create, host, and play quiz-based games in class and host game-based homework in learning management systems. Gimkit was introduced in 2 dental hygiene courses at a Canadian university: one was offered in person; the other was asynchronous online. This study aimed to explore students' perception of game-based learning experiences, their choice of game modes, and their source of motivation. Methods: Students from the second and third years of the dental hygiene program were invited to participate in a voluntary online survey to collect their perceptions of either the live quiz game or the game-based homework assignments, their choice of game mode, and their motivation to play. Descriptive statistics were applied to analyze the survey data. Results: Thirty-five percent (n = 15) of the in-person class and thirty percent (n = 14) of the online class completed the voluntary survey. All participants from the online and in-person groups strongly agreed that they improved their knowledge by playing the game. Discussion: Students were largely motivated extrinsically and played the game to learn course content. Students from the in-person class were driven towards Gimkit live quiz games by in-class competition. For online students, the "challenge of the game" was the most attractive feature of Gimkit. Conclusion: Game-based learning with Gimkit can motivate dental hygiene students and promote self-determination.